Planning for modular and hybrid fixtures - Wallack, A.S.; Canny, J.F. (Robotics and Automation, '94 International Conference, 1994)
Fixturing is a fundamental problem in mechanical assembly. Usually, two and a half dimensional objects can be fixtured in many different ways using a fixture vice, especially if pegs of different radii are available. The authors present an algorithm which enumerates all force closure fixture vice configurations and corresponding object poses. Automatic fixture design algorithms are essential for planning because optimal fixturing selections for multiple operations requires examining all of the valid configurations. The algorithm runs in O(A) time, where A is the number of configurations which simultaneously contact the object.< >